Women and the Covid-19 Pandemic (Women's Multiple Roles during the Covid-19 Pandemic) - Muh. Khaerul Watoni A; Wilodati Wilodati; Elly Malihah (International Journal of Social Service and Research, 2023)
The purpose of this paper is to determine the dual role of women during a pandemi and its causative faktors, this study uses qualitative methods with literary study techniques, the findings of this discussion are that basically women have a major role as someone who works in the domestic sphere, but because of the pandemi. Covid-19 causes women to have educational and economic functions, which means that there is an additional dual role for women during the pandemi, who initially only became housewives and worked. The faktors that cause the dual role of women are divided into 2, namely: internal and external faktors, where internal faktors include motivation and personality maturity. Then the external faktors include economy, culture and environment.